Pomiędzy spojrzeniem a dotykiem: trajektorie tatrzańskie Mirosława Koprowskiego - Wielechowska, Katarzyna (Relacyjność w kulturze i sztuce: Księga jubileuszowa Profesor Małgorzaty Leyko, 2025)
The text is an attempt to tell a story about the experience of a painter and a moun-taineer, about the interpenetration of two practices: mountaineering and landscape painting, about the realisation in this way of an intense and essentially intimate de-sire to be in the world of Tatra nature. The methodological framework for the story is Stephen Greenblatt’s concept of awe and response, which is simultaneously sub-jected to a reinterpretation - the level of response here is determined not by the cul-tural context, but by the context of Tatra nature, in which the practice of the painter and mountaineer is embedded. Reflections on Miroslaw Koprowski’s relationship with the universe of Tatra nature, on the interdependence of painting and moun-taineering, on haptics and optics, and on performance as a dynamic connection be-tween the human and the non-human are made primarily with reference to Maurice Merleau-Ponty’s non-anthropocentric reflection.